2021
DOI: 10.1055/a-1537-9886
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to Intermittent vs. Continuous Blood Flow Restriction Training: A meta-Analysis

Abstract: The proven beneficial effects of low-load blood flow restriction training on strength gain has led to further exploration into its application during rehabilitation, where the traditional use of heavy loads may not be feasible. With current evidence showing that low-load blood flow restriction training may be less well tolerated than heavy-load resistance training, this review was conducted to decipher whether i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
(133 reference statements)
0
4
0
Order By: Relevance
“…The mean and SD of the final set performed in each training session were chosen for the analyses, as performed in a previously published systematic review. 61 When the study reported both local and overall RPE values, only the overall RPE was considered for the analyses. The standardized mean difference (SMD) and SE were extracted from individual studies and pooled using the generic inverse variance method.…”
Section: Methodsmentioning
confidence: 99%
“…The mean and SD of the final set performed in each training session were chosen for the analyses, as performed in a previously published systematic review. 61 When the study reported both local and overall RPE values, only the overall RPE was considered for the analyses. The standardized mean difference (SMD) and SE were extracted from individual studies and pooled using the generic inverse variance method.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, however, Individualized pressure appears to be widely accepted owing to its logical basis, but it does not justify the choice of individualized pressure when setting up a BFR-RT exercise program, and more theoretical support needs to be found for the use of individualized pressure for BFR-RT (Clarkson et al, 2020). Another related meta-analysis (Sinclair et al, 2022) described that the cuff inflation pattern (continuous and intermittent pressure) was not a variable affecting muscle strength gain, but the results of the analysis were limited to two articles, entailed limited guidance value in terms of enhancing muscle strength with BFR-RT interventions that use different cuff inflation patterns. In addition.…”
Section: Introductionmentioning
confidence: 99%
“…In the G RTBFR, cuffs were deflated between sets and exercise intervals to restore normal limb circulation, as additional care for PWH. This intermittent BFR favors a better rate of perceived exertion 29 .
Figure 2 Training protocol and assessments during the intervention period.
…”
Section: Methodsmentioning
confidence: 90%